2018
DOI: 10.18410/jebmh/2018/266
|View full text |Cite
|
Sign up to set email alerts
|

Medical Termination of Pregnancy: Six Years Study of the Trend and Profile of the Clients in a Metropolitan Public Hospital

Abstract: BACKGROUND To increase the incidence of safe and legalised abortions, it is important to know the clients. This study is a 6 years research of the records of MTP performed at the public hospital attached to a medical college, to know the trend, socio-demographic and obstetric status of the women undergoing MTP. The objectives of the study were to find trend, sociodemographic factors, obstetric status and complications of MTPs. MATERIALS AND METHODS A study of the records of all the MTP operations performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…15 Yet another study from Maharashtra reported contraceptive failure in 99.1% as reason for undergoing MTP. 16 In the indication of humanitarian grounds all the 28 subjects were rape victims in this study and majority were second trimester pregnancies. No one was denied of abortion services though it is reported that the rape victims suffer denial of safe abortion in public sectors in India due to misinterpretation of MTP Act rules and regulations.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…15 Yet another study from Maharashtra reported contraceptive failure in 99.1% as reason for undergoing MTP. 16 In the indication of humanitarian grounds all the 28 subjects were rape victims in this study and majority were second trimester pregnancies. No one was denied of abortion services though it is reported that the rape victims suffer denial of safe abortion in public sectors in India due to misinterpretation of MTP Act rules and regulations.…”
Section: Discussionmentioning
confidence: 74%
“…[3][4][5] Oral contraception was the choice of contraception in most women in North India where as tubectomy or CU-T in South India. 3,4,16…”
Section: Discussionmentioning
confidence: 99%